2021
DOI: 10.1007/s10567-021-00350-8
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Facilitator Competent Adherence Used in Parenting Programs and Their Psychometric Properties: A Systematic Review

Abstract: Implementation fidelity is a critical component of intervention science, which aims to understand how interventions unfold in practice to improve outcomes. A key element of fidelity is facilitator competent adherence—the extent to which a program is delivered as prescribed with the specified level of quality. We conducted a two-part systematic review examining these aspects in parenting programs aiming to reduce child behavior problems and maltreatment. Part One reviews measures of facilitator competent adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 61 publications
(96 reference statements)
0
25
0
2
Order By: Relevance
“…Além disso, a implementação deve apresentar sustentabilidade que é fundamental para compreensão dos efeitos dos programas, a longo prazo (Bowman et al, 2008). Outro aspecto a ser considerado na implementação de programas é a fidelidade à proposta original que requer a avaliação da atuação dos facilitadores quanto à aderência ao programa e à competência dos facilitadores (Martin et al, 2021). Esses aspectos podem ser avaliados por meio da observação do comportamento por videogravação (Martin et al, 2021).…”
Section: Como Avaliar Os Indicadores Da Implementação Do Programa Act...unclassified
“…Além disso, a implementação deve apresentar sustentabilidade que é fundamental para compreensão dos efeitos dos programas, a longo prazo (Bowman et al, 2008). Outro aspecto a ser considerado na implementação de programas é a fidelidade à proposta original que requer a avaliação da atuação dos facilitadores quanto à aderência ao programa e à competência dos facilitadores (Martin et al, 2021). Esses aspectos podem ser avaliados por meio da observação do comportamento por videogravação (Martin et al, 2021).…”
Section: Como Avaliar Os Indicadores Da Implementação Do Programa Act...unclassified
“…Relaciona-se à aderência, ao desenho e protocolos de determinado programa, o que se torna um elemento chave para qualquer disseminação e escalabilidade do programa. A fidelidade deve ser avaliada por meio da atuação dos facilitadores, por meio da observação do comportamento por videogravação ou autorrelato, a fim de identificar o grau de aderência ao conteúdo e estratégias do programa e a competência dos facilitadores (Martin et al, 2021). Certamente, o guia de implementação do programa ajuda na manutenção da fidelidade ao programa original durante sua implementação na prática.…”
Section: Ciclos Rápidos E Repetidos E Estudo Piloto No Processo De In...unclassified
“…Fidelity of an intervention can broadly be defined as “the intervention being delivered as intended by the program developers and consistent with the program model” (Breitenstein et al , 2010, p. 2). Some authors distinguish between adherence (the degree to which prescribed intervention activities and strategies are used) and competence (the skill and style with which the program is delivered; Martin et al , 2021). Assessing fidelity is important not only to support the training and development of practitioners (called “facilitators” in the RFP), but also as a way of assessing whether the intervention has been delivered in a way that is consistent with the core principles and techniques of the approach.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review of fidelity measures in parenting programmes (Martin et al , 2021) identified 65 such measures, none of which were specifically identified as exclusively targeted at assessing parenting programmes for foster carers. However, some of the identified programmes, such as the Triple P, Incredible Years and Parent Management Training Programme – Oregon Model interventions have been used with foster carer populations and evaluated for fidelity (Maaskant et al , 2016; Job et al , 2022; McDaniel et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation